Diagnosis and Treatment of Neurocysticercosis - Nash, Theodore E. (2011)
Neurocysticercosis, a major cause of acquired seizures and epiilepsy, is caused by infection with the larval cystic form of the tapeworm, Taenia solium. CT and MRI imaging, development of sensitive and specific diagnostic methods, and discovery of relatively effective anti-cestode drugs, revolutionized knowledge of the burden of infection and disease and led to effective treatments. Here we review the rationale of treatment, the essential role of inflammation in the genesis of disease and its exacerbation as a result of anti-parasitic treatment, and limitations in the efficacy of current anti-parasitic and anti-inflammatory treatments. The importance of “end stage” calcified granulomas as foci of seizures and epilepsy with and without perilesional edema in endemic populations has recently been recognized. New information indicates perilesional inflammation around some calcified foci is associated with seizures and perilesional edema, which suggests that anti-inflammatory treatments may play a role in controlling or preventing epilepsy in these patients. Most importantly, neurocysticercosis is one of the few diseases that can be eradicated, an accomplishment that would prevent millions of cases of epilepsy.